2006
DOI: 10.1007/s10546-005-9019-3
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency and the Exchange of Scalars in the Nocturnal Surface Layer

Abstract: The determination of nocturnal surface fluxes in low wind conditions is a major problem for micrometeorological studies. The eddy correlation technique, extensively used in field measurements, becomes inappropriate if not enough turbulent activity exists. At the same time, the phenomenon of turbulence intermittency is responsible for the existence of localized events of short duration within which a large fraction of the total nighttime scalar exchange occurs. The scalar flux within a certain intermittent even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…These were rather short time periods in comparison to those observed at other sites, especially flat terrain sites, where a LLJ can last throughout the night until the beginning of dawn (e.g., Whiteman et al, 1997;Banta et al, 2007;Duarte et al, 2012). On the other hand, the shortest duration of a jet period (30 min) was too long to be explained only by the occurrence of gusts (Acevedo et al, 2006), and the vertical wind profiles provided no indication of gusts during jet periods. Results of Pinto et al (2006) and Chiao and Dumais (2013) from the VTMX and T-REX project, respectively, showed longer duration and larger depth of the detected jets on a larger topographic scale.…”
Section: Duration and Ending Of Jet Periodsmentioning
confidence: 70%
See 1 more Smart Citation
“…These were rather short time periods in comparison to those observed at other sites, especially flat terrain sites, where a LLJ can last throughout the night until the beginning of dawn (e.g., Whiteman et al, 1997;Banta et al, 2007;Duarte et al, 2012). On the other hand, the shortest duration of a jet period (30 min) was too long to be explained only by the occurrence of gusts (Acevedo et al, 2006), and the vertical wind profiles provided no indication of gusts during jet periods. Results of Pinto et al (2006) and Chiao and Dumais (2013) from the VTMX and T-REX project, respectively, showed longer duration and larger depth of the detected jets on a larger topographic scale.…”
Section: Duration and Ending Of Jet Periodsmentioning
confidence: 70%
“…This intermittent turbulence plays a major role in estimating nocturnal exchange of, e.g., CO 2 , but there is no consensus on how to treat longer time series when intermittent turbulence occurs at times. Variable data window sizes can lead to an increase of estimated turbulent energy and mass fluxes of 10 to 15 % (Acevedo et al, 2006). Mauder et al (2013) address the difficulty to identify intermittency within eddy-covariance (EC) data sets.…”
Section: Introductionmentioning
confidence: 99%
“…This is a feature of all atmospheric chemistry models, while observations show that nocturnal intermittent transport events actually occur regularly. For example, observations by Fitzjarrald and Moore (1990) and Acevedo et al (2006) provide evidence of the important role of nocturnal intermittent turbulent transport in tropical forest exchanges of energy, moisture and CO 2 . Fitzjarrald and Moore (1990) postulated a mechanism to explain this intermittent exchange regime by the breakdown of the nighttime inversion through enhanced shear associated with the presence of a nocturnal jet.…”
Section: Volatile Organic Compounds: Isoprene and Oxidation Productsmentioning
confidence: 99%
“…Howell and Sun (1999) define intermittency in terms of the fraction of the record required to account for a certain fraction of the total flux, which emphasizes the larger transporting eddies. Following Howell and Sun (1999), a number of studies, including Coulter and Doran (2002), Acevedo et al (2006), Basu et al (2006), have documented the flux intermittency for a variety of situations in the stable boundary layer. More complex event-finding procedures were applied in Nakamura and Mahrt (2005), who showed that the horizontal scale of intermittent mixing events was often on the order of 100 m or less.…”
mentioning
confidence: 99%